In situ x-ray tomography characterisation of 3D deformation of C/C-SiC composites loaded under tension - Chen, Y; Shi, Y; Chateau, C; Marrow, T (Elsevier, 2021)
C/C-SiC composites fabricated through Liquid Silicon Infiltration were tested under monotonic tension with in situ X-ray computed tomography. The specimens had different fibre orientations with respect to the tensile direction, 0°/90° and ±45°, such that the tension accounted for in-axis and off-axis loads, respectively. The 3D XCT images provided explicit visualisations and quantitative measurements of the distributions of SiC-Si and the orientations of the C fibre bundles. The full-field displacement and strain fields were measured by Digital Volume Correlation, observing a difference in the local deformations in response to the in-axis and off-axis loading. In both specimens, the tensile load triggered significant strain localisations at low stress (<50 MPa). Strong local deformations, observed at both low and high applied stresses, were mostly in the through-thickness direction, indicating local delamination. These observations show the importance of residual stresses to damage development in C/C-SiC composites.